2015
DOI: 10.1096/fj.14-259531
|View full text |Cite
|
Sign up to set email alerts
|

Transient delivery of modified mRNA encoding TERT rapidly extends telomeres in human cells

Abstract: Telomere extension has been proposed as a means to improve cell culture and tissue engineering and to treat disease. However, telomere extension by nonviral, nonintegrating methods remains inefficient. Here we report that delivery of modified mRNA encoding TERT to human fibroblasts and myoblasts increases telomerase activity transiently (24-48 h) and rapidly extends telomeres, after which telomeres resume shortening. Three successive transfections over a 4 d period extended telomeres up to 0.9 kb in a cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 78 publications
1
72
1
1
Order By: Relevance
“…In addition, we found that telomerase signaling genes were affected by coculture. Although hTERT is not typically expressed in somatic cells, low expression levels are thought to slow telomere shortening in adult stem cells (56) and exogenous addition of hTERT mRNA extends telomeres and the life span of epidermal keratinocytes in vitro (57). The apparent stabilization of telomere length during 3T31Y culture supports our view that basal stem cells are better preserved.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, we found that telomerase signaling genes were affected by coculture. Although hTERT is not typically expressed in somatic cells, low expression levels are thought to slow telomere shortening in adult stem cells (56) and exogenous addition of hTERT mRNA extends telomeres and the life span of epidermal keratinocytes in vitro (57). The apparent stabilization of telomere length during 3T31Y culture supports our view that basal stem cells are better preserved.…”
Section: Discussionmentioning
confidence: 52%
“…If telomere extension can increase cell proliferative capacity in vitro (Ramunas et al, 2015) and account for the reversal of tissue degeneration in mice (Jaskelioff et al, 2011), than there is the possibility of being used to attenuate the rate of aging. That is certainly the core concept behind the commercialization, by some companies, of telomere measurement kits (Wolinsky, 2011), aimed at estimating the biological age of individuals and, to some extent, the risk of developing telomere shortening-associated diseases, such as atherosclerosis (Samani et al, 2001), coronary heart diseases (Ogami et al, 2004) and liver cirrhosis (Wiemann et al, 2002).…”
Section: Aging Therapies—cure Aging or Die Trying?mentioning
confidence: 99%
“…Remarkably, telomere shortening occurs in the heart independently of cell division (Chang et al, 2016). Blau's laboratory has developed a transient modified mRNA approach to deliver TERT for only 48 h, which overcomes problems associated with constitutive retroviral delivery, and leads to a marked increase in telomere length and rescue of cell proliferative defects (Ramunas et al, 2015). Finally, Saul Villeda (UCSF, USA), who explores the mechanisms of brain ageing, used mouse parabiosis experiments to show that β2-microglobulin (B2M) is a brain ageing factor, the action of which is mediated by the MHC (Smith et al, 2015).…”
Section: Senescence Regeneration and Ageingmentioning
confidence: 99%